Efeito de um protocolo de exercícios de curto prazo, baseado no método pilates, sobre o estresse xidativo e funcionalidade de diabéticos tipo 2 - Gouveia, Samara Sousa Vasconcelos (2019)
This study was based on an interest in analyzing the effect that an exercise protocol based on the Pilates method would have on the variables indicative of oxidative stress and functionality in patients with type 2 diabetes mellitus. Methodology: This was a randomized clinical trial having as target population type 2 diabetics, resident in Parnaíba-PI, enrolled in Hiperdia. An exercise protocol, based on the Pilates method, was carried out, with a duration of 8 weeks, with 2 visits per week. The variables evaluated were: vital signs and blood glucose, respiratory muscle strength (Pimáx and Pemáx), stabilometry, electromyography, heart rate variability and serum glucose levels, glycated hemoglobin, lipid profile, C-reactive protein and malondialdehyde. The results were expressed as mean ± standard deviation for continuous variables and frequency and percentage for categorical variables. All variables were tested for normal distribution. The Tukey post hoc ANOVA test was used for the variables with normal distribution, and the Kruskal-Wallis, Wilcoxon, Friedman and Spearman correlation tests were used for the variables that did not present a normal distribution, with a significance level of 5%, for through SPSS 21.0. Results: A total of 44 type 2 diabetic patients (intervention group: 22, control group: 22), with a mean age of 61.23 ± 8.49 years, were the majority (77.3%), married or in (59.1%) and literacy (31.8%), with a mean BMI of 26.96 ± 4.35 kg / m2. When analyzing the effect of the protocol on vital signs and blood glucose, vital signs did not change significantly, and there was a significant reduction in blood glucose of 16mg / dL (p = 0.00). Regarding the respiratory variables, there was no difference between Pimax and Pemax. In the stabilometry with open eyes, there was reduction of the anteroposterior mean position (p = 0.008) and the mean anteroposterior frequency (p = 0.039). With the eyes closed, there was a reduction of the anteroposterior (p = 0.018) and mediolateral mean position (p = 0.048), total displacement (p = 0.022) and anteroposterior velocity (p = 0.022). On electromyography, there were no significant differences. There were differences in cardiac variability in the time domain for Mean RR (p = 0.00), SDNN (p = 0.001), RRtri (p = 0.00) and TINN (0.001), and a significant increase for the variable SD2 of the Poincaré geometric index (p = 0.001). In the biochemical analyzes, there was a significant reduction of glycated hemoglobin (p = 0.002) and oxidative stress (p = 0.004). Conclusion: The exercise protocol based on the Pilates method produced the reduction of postprandial glycemia and glycated hemoglobin and oxidative stress and stabilometric changes and autonomic modulation. Keywords: Diabetes Mellitus. Exercise Movement Techniques. Biomarkes. Oxidative Stress.